Distal tibial reconstruction with use of a circular external fixator and an intramedullary Nail. the combine technique - Eralp, Levent; Kocaoglu, Mehmet; Mohd Yusof, Nazri; Bulbul, Murat (The Journal of Bone and Joint Surgery, 2007)
Background: Distal tibial reconstruction with use of an external fixator when there is bone loss, limb-length discrepancy, and/or ankle instability is associated with many problems. The technique of limb-lengthening, ankle arthrodesis, and segmental transfer over an intramedullary nail has been introduced to overcome these problems. The present study investigates this combined technique. Methods: Between 2002 and 2005, six patients, who ranged from seventeen to seventy years old, underwent distal tibial reconstruction and ankle arthrodesis with use of a circular external fixator and an intramedullary nail to treat a distal tibial defect following resection for chronic osteomyelitis or tumor or to treat a limb-length discrepancy combined with ankle instability. Functional and radiographic results were evaluated, with use of the criteria described by Paley et al., at an average follow-up of thirty-four months. Results: The mean size of the bone defects in three patients was 5.3 cm (2, 7, and 7 cm), and the mean amount of the limb-shortening in four patients was 5.25 cm (range, 4 to 6 cm). The mean external fixation time was 3.5 months, and the mean external fixator index was 0.57 mo/cm. There was no recurrence of infection in the two patients with osteomyelitis. All six patients had excellent bone results, and the functional results were excellent for two patients and good for four patients. There were four complications, three of which were categorized, according to Paley, as a problem (a difficulty that occurs during lengthening and is resolved without operative intervention) and one that was categorized as an obstacle (a difficulty that occurs during lengthening and needs operative treatment). Conclusions: The combined technique is an improvement over the classic external fixation techniques of distal tibial reconstruction with ankle arthrodesis. It reduces the duration of external fixation, thus increasing patient acceptance, and it is associated with a low complication rate facilitating more rapid rehabilitation.